Mental Health Management & Work Life Balance Generasi Milenium Terhadap Kemungkinan untuk Berpindah Kerja Karyawan - Anifa Seviana; Rudi Suryo Kristanto (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Research on the behavior of the millennial generation is very interesting to always study. Moreover, many survey institutions in the HRM sector, such as Deloitte and Gallup, have found that there is a tendency for the millennial generation to transfer jobs from one company to another (turn over). This research intends to examine the factors that influence an employee to have a tendency to change jobs (intention turnover), namely Mental Health and Work Life Balance. By taking 144 millennial employee respondents, the results showed that these two factors had a strong influence on the desire to resign (turn over).